(untitled) (Ágora Journal, 2021)
The captaincy of Itamaracá stayed as a donatarial captaincy, in a period in which the captaincies hereditaries of the Atlantic progressively were returning to the royal heritage during the seventeenth and eighteenth centuries. After the return the captaincy to donatarial family of the Cascais’ Marquises, in 1692, until the death of the last heiress of Cascais’ House, in 1763. In this article, we try to understand how the Cascais’ Marquis maintained the administration of his possession at a distance, through the appointments to offices of the colonial administration, especially the office of captain-mor on the government, as well as attorneis of the donatory, often coinciding with the captain-mor.